Larval collectors network documents the spread of the invasive bivalve Pinctada radiata in the Mediterranean Sea - Júlia García-Colomé; Iris E. Hendriks; Isabel Abel-Abellán; Giorgio Aglieri; Peru Agueda; Natalia Aisa-Bravo; Elvira Álvarez; María P. Andrada-Nicolás; Irene Antón-Linares; Elisa Arroyo-Martínez; Carolina Audisio-Pacheco; Tatjana Bakran-Petricioli; et al. (Marine Environmental Research, 2026)

DiverReef : A global database of the behavior of recreational divers and their interactions with reefs over 20 years - Vinicius J. Giglio; Johnatas Adelir‐Alves; Natalia Balzaretti Merino; Myrna Leticia Bravo‐Olivas; Emma F. Camp; Edoardo Casoli; Rosa Maria Chávez‐Dagostino; Eliana Ferretti; Douglas Fraser; Ana C. Grillo; Santiago Jiménez‐Guiérrez; Kelen L. Leite; et al. (Ecology, 2025)
Recreational diving is an important activity in reef environments worldwide, providing income and employment for coastal communities and connecting visiting divers to these ecosystems promoting conservation and stewardship. However, if poorly managed, diving has the potential to cause detrimental effects on benthic communities via mechanical damage caused by physical contact of divers with the reef, often in the form of unintentional fin kicks resulting from poor buoyancy. Understanding diver–reef interaction patterns is important to elucidate the potential impacts of diving tourism on the reef biota. The DiverReef database provides the first public dataset on the underwater behavior of recreational divers in shallow reef environments (

High spatial resolution photo mosaicking for the monitoring of coralligenous reefs - E. Casoli; D. Ventura; G. Mancini; D. S. Pace; A. Belluscio; G. Ardizzone (Coral Reefs, 2021)
Coralligenous reefs are characterized by large bathymetric and spatial distribution, as well as heterogeneity; in shallow environments, they develop mainly on vertical and sub-vertical rocky walls. Mainly diver-based techniques are carried out to gain detailed information on such habitats. Here, we propose a non-destructive and multi-purpose photo mosaicking method to study and monitor coralligenous reefs developing on vertical walls. High-pixel resolution images using three different commercial cameras were acquired on a 10 m 2 reef, to compare the effectiveness of photomosaic method to the traditional photoquadrats technique in quantifying the coralligenous assemblage. Results showed very high spatial resolution and accuracy among the photomosaic acquired with different cameras and no significant differences with photoquadrats in assessing the assemblage composition. Despite the large difference in costs of each recording apparatus, little differences emerged from the assemblage characterization: through the analysis of the three photomosaics twelve taxa/morphological categories covered 97–99% of the sampled surface. Photo mosaicking represents a low-cost method that minimizes the time spent underwater by divers and capable of providing new opportunities for further studies on shallow coralligenous reefs.

A massive ingression of the alien species Mytilus edulis L. (Bivalvia: Mollusca) into the Mediterranean Sea following the Costa Concordia cruise-ship disaster - E. CASOLI; D. VENTURA; M. V. MODICA; A. BELLUSCIO; M. CAPELLO; M. OLIVERIO; G. ARDIZZONE (Mediterranean Marine Science, 2016)
The Costa Concordia cruise-ship disaster occurred just off the coast of Italy on January 13th, 2012, and entailed the largest marine salvage operation in history. The salvage employed vessels from different European harbours, providing an unexpected means for transporting alien species into the Mediterranean. In this work we identified mussel species using fragments length polymorphism of a nuclear locus and report the first evidence of the transport of the blue mussel, Mytilus edulis Linnaeus, 1758 (Bivalvia: Mollusca), into the Mediterranean Sea, as a part of the fouling community of the hull of an accommodation barge arrived from a NE Atlantic location in October 2012. Furthermore, we describe the rapid growth of this species, under the ASV Pioneer, until its almost total extinction during the summer of 2013, which left a covering of mussel shells on the underlying Posidonia oceanica (Linnaeus) Delile, 1813. meadow. This high mortality rate indicated that M. edulis had been exposed to high stress conditions, probably due to different salinity, temperature, and oligotrophic conditions from its place of origin, and there was no spawning event or known settlement on the nearest infralittoral natural habitats. This event reminds us of how the Mediterranean Sea is constantly under alien-species pressure, due to human activities.

Wild Ungulate Slaughtering and Meat Inspection - C. Casoli; E. Duranti; F. Cambiotti; P. Avellini (Veterinary Research Communications, 2005)